ИЗУЧЕНИЕ ВЛИЯНИЯ КОНЦЕНТРАЦИИ МОЧЕВОЙ КИСЛОТЫ С ГИПЕРУРИКЕМИЕЙ В СЫВОРОТКЕ КРОВИ И МОЧЕ ПРИ ЭКСПЕРИМЕНТЕ (Scientific journal of the Fergana State University, 2023)
In recent years, a large number of reports have appeared on the association of elevated serum uric acid levels with the risk of progression of arterial hypertension, ischemic heart disease, and a prognosis in patients with these diseases. At the same time, there is a small amount of work devoted to the clinical and prognostic value of hyperuricemia in chronic heart failure, although this pathology remains one of the unfavorable prognosis in the series of cardiovascular imperfections.